Enigmatic plesiosaur vertebral remains from the middle Turonian of Germany. (June 2020) - Sachs, Sven; Madzia, Daniel; Püttmann, Tobias; Kear, Benjamin P.
Abstract: The Turonian (93.9–89.8 Ma) was a key transitional interval of plesiosaur evolution, during which pliosaurid apex predators (dominant since the Middle Jurassic) rapidly declined, and polycotylids correspondingly radiated as middle trophic-level pursuit hunters. Paradoxically, however, the fossil record of Turonian plesiosaurs is globally sparse, especially in continental Europe where only a handful of fragmentary specimens have been recovered from localities in the Czech Republic, Germany and Poland. Here, we report on a new European Turonian plesiosaur occurrence from the Bochum Grünsand Member of the Duisburg Formation in the city of Unna, western Germany. These remains comprise a series of eight mid-series cervical vertebrae with articulated ribs that can be precisely correlated to the lower middle Turonian UC8a–UC8b calcareous nannofossil biozones. The vertebrae display a distinctive character state combination, including transversely broad lozenge-shaped centra that are anteroposteriorly compact, bear amphicoelous articular surfaces, inset lateral sides, and large zygapophyses that are broader than the corresponding centra. Although phylogenetically inconclusive, these features are compatible with coeval polycotylids. The Bochum Grünsand Member vertebrae thus augment the currently scant knowledge of Turonian plesiosaurs from Europe, and support assertions that the regional assemblage was taxonomically diverse at that time.